Professional Directors and Governance Quality - Wahid, Aida Sijamic; Welch, Kyle; Maber, David A. (Contemporary Accounting Research, 2019)
ABSTRACT We examine professional directors—board members with no employment outside of serving as independent directors. We find that boards with a higher percentage of professional directors engage in more acquisitions, experience lower acquisition announcement returns, and exhibit lower performance‐turnover sensitivity and lower financial performance. We also examine the returns surrounding the appointment‐announcement dates of professional directors and find that firms experience significantly lower cumulative abnormal returns upon the appointment announcement of professional directors as compared to nonprofessional directors. The negative returns are primarily experienced by firms that face greater agency issues, suggesting that the market does not value professional directors for stricter monitoring. Overall, our findings do not lend support for calls to professionalize corporate boards.